Pharmacokinetics and Drug Metabolism in Canada: The Current Landscape—A Summary of This Indispensable Special Issue - Neal M. Davies; Kishor M. Wasan (Pharmaceutics, 2018)
Canadian Pharmaceutical Scientists have a rich history of groundbreaking research in pharmacokinetics and drug metabolism undertaken primarily throughout its Pharmacy Faculties and within the Pharmaceutical and Biotechnology industry.[...]